Prevalence of factors associated with edentulousness (no natural teeth) in adults with intellectual disabilities. Issue 12 (6th May 2019) - Kinnear, D.; Allan, L.; Morrison, J.; Finlayson, J.; Sherriff, A.; Macpherson, L.; Henderson, A.; Ward, L.; Muir, M.; Cooper, S. A.
Abstract: Background: Poor oral health is largely preventable. Prevention includes toothbrushing and regular dental checks. Oral health has important consequences for general nutrition, chewing, communication, wider systemic disease, self‐confidence and participation in society. This study investigated the prevalence of edentulousness (no natural teeth) in adults with intellectual disabilities (IDs) compared with the general population and associated factors. Methods: An adult cohort with IDs residing in Greater Glasgow and Clyde, Scotland, underwent detailed health assessments between 2002 and 2004. Between 2004 and 2006, a subsample had an oral check. Data on edentulousness in the cohort were compared with adult participants from Greater Glasgow and Clyde in the 2008 Scottish Health Survey. Within the IDs cohort, binary logistic regression analyses investigated potential relationships between edentulousness and demographic and clinical factors. Results: Five hundred sixty adults with IDs were examined [53.2% (298) male, mean age = 46.3 years, range 18–81 years] and compared with 2547 general population: edentulousness was 9% vs. 1% aged 25–34 years; 22% vs. 2% aged 35–44 years; 39% vs. 7% aged 45–54 years; 41% vs. 18% aged 55–64 years; and 76% vs. 34% aged 65–74 years. In both groups, edentulousness increased with age. After stratification for age, rates of edentulousness were consistently higher in the ID cohort. Odds ratios within age strata were not homogenous (Mantel–Haenszel test, P  < 0.0001). Edentulousness was more likely in those with more severe IDs (adjusted odds ratio (AOR) = 2.36; 95% confidence interval (CI) [1.23 to 4.51]); those taking antipsychotics (AOR = 2.09; 95% CI [1.25 to 3.51]) and those living in the most deprived neighbourhoods (AOR = 2.69; 95% CI [1.11 to 6.50]). There was insufficient evidence for associations with sex, type of accommodation/support, antiepileptics, problem behaviours or autism. Conclusions: Adults with IDs have a high prevalence of edentulousness and need supported daily oral care to reduce the need for extractions. Despite previous reports on poor oral care and the move towards person‐centred care, carers and care‐giving organisations need greater support to implement daily oral care. Prescribers need awareness of the potentially contributory role of antipsychotics, which may relate to xerostomia.